If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4(x + -5) = -2(-2 + -1x) + 5 Reorder the terms: -1x + 4(-5 + x) = -2(-2 + -1x) + 5 -1x + (-5 * 4 + x * 4) = -2(-2 + -1x) + 5 -1x + (-20 + 4x) = -2(-2 + -1x) + 5 Reorder the terms: -20 + -1x + 4x = -2(-2 + -1x) + 5 Combine like terms: -1x + 4x = 3x -20 + 3x = -2(-2 + -1x) + 5 -20 + 3x = (-2 * -2 + -1x * -2) + 5 -20 + 3x = (4 + 2x) + 5 Reorder the terms: -20 + 3x = 4 + 5 + 2x Combine like terms: 4 + 5 = 9 -20 + 3x = 9 + 2x Solving -20 + 3x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -20 + 3x + -2x = 9 + 2x + -2x Combine like terms: 3x + -2x = 1x -20 + 1x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 -20 + 1x = 9 + 0 -20 + 1x = 9 Add '20' to each side of the equation. -20 + 20 + 1x = 9 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = 9 + 20 1x = 9 + 20 Combine like terms: 9 + 20 = 29 1x = 29 Divide each side by '1'. x = 29 Simplifying x = 29
| 2h-9/3=3 | | 8a-9=87 | | X*20=57 | | 15+5m=45 | | x^2-2x=26 | | 25x+45=-65 | | x+2=x*3 | | 10-23x=17 | | 7t-7=35 | | -2x-4(x+1)=5x+9 | | -2(3x+4)-x+6=-5x-2 | | 2(x+3)=(x-3) | | 23x-10=17 | | 8=4-2x | | 153.92/4 | | 2+p=9 | | 32-3x=12+7x | | 22+11=4x-7 | | 2x+33=63 | | 9.25x+1=10x+1 | | 0=x(2x-3)(4x+1) | | 5x+4=13+2x | | x/9-8=-5 | | 0.3x^2-48x+24=0 | | 58x=870 | | 9.25x=10x | | 2(3x+4)+8=-5x-4+9 | | 2-q/36 | | -51t=65t | | -51=65t | | 3x-4=3x-8 | | 5z^2+30z-275=0 |